Property Tax and Quality of Life in the Czech Municipalities: Does the Policy of Raising Local Coefficient Imply Potential or Risk for Development? - Pavel Zdražil; Bohuslav Pernica (Review of Economic Perspectives, 2018)
Since the 1990s, the Czech intergovernmental fiscal relations have been undergoing a transformation. One of the measurements strengthening the autonomy of local authorities was the introduction of the instrument of the local coefficient in 2009 which provided the municipalities with the possibility to raise real estate tax in order to maximize their revenues. The aim of this article is to statistically analyse the impact of this instrument on the quality of life in a sample of Czech municipalities which have changed the local coefficient from 1 up to 5. The empirical analysis consists of two parts - a non-parametrical correlation analysis and paired difference testing. It is carried out in context of population ageing versus population growth, and the availability of basic public services (education, health care, communication, public safety). The analysis proves that there are great differences between the municipalities that have increased the real estate taxes and municipalities that have not. In the second case, the municipalities are more threatened by population ageing as they face the growth of population while the number of working age citizens is declining together with the provision of public services. Meanwhile, the municipalities that have increased the coefficient of real estate taxes have experienced increase in both population and working age population sizes. Such municipalities do not face the problem of shrinking of public services. Also, the policy of raising local coefficient implies a potential for ongoing development of districts.
Keywords: 330; local coefficient; local government; municipality; quality of live; property tax